(untitled) (Journal of the College of Basic Education, 2022)
The art of making fabrics has become one of the industries that many countries that seek to achieve its economic growth depend on and its civilizational presence. Therefore, it was linked to the scientific and technical development taking place in all human aspects. The appearance of harmony with the environmental, psychological and physiological aspects, and this choice differs from one gender to another, and this is embodied in the designs of contemporary fabrics. T express check integrated personal attraction and excitement of the recipient So the designer must study the social and physiological systems systems of the recipient to achieve a special technical culture that works to harmonize with contemporary fabric designs according to the concept of epistemology. Here the designer can predict and know the ability of these designs to achieve functional and aesthetic performance according to the characteristics of technical culture to achieve inclusivity in proliferation within multiple societies, as it came The research is consistent with this interest to know the role of epistemology and technology culture in contemporary fabric designs to achieve the design goal.